Emotional design in ICT resources for learning: A systematic review (Papeles, 2026)
Introduction: The objective of this article is to present the results of a systematic literature review on emotional design applied to ICT resources for learning, describe its main results and its contributions in the last decade. Methodology: The Prisma 2020 Declaration was followed with inclusion and exclusion criteria to carry out this exploratory qualitative study. A total of 29 articles from the DOAJ, Web of Science, ERIC, and Science Direct databases were analyzed in the search period between 2015-2025. Results and Discussion: The results show a growing interest since 2018, mainly in multimedia materials and in the use of color and anthropomorphism. Among the contributions are improvement in motivation, decrease in perceived difficulty and improved learning. Conclusions: The emotional design applied to ICT resources for learning improves retention, transfer and motivation in students. Regarding the generation of emotions, the results are mainly positive. It is important to apply it to other types of ICT resources, as well as evaluate other concepts in addition to the generation of emotions such as user experience.
Keywords: Emotional design; learning; ICT resources; systematic review; educational technology